Model Pembelajaran Advance Organizer: Dampak Terhadap Hasil Belajar Kognitif Peserta Didik - Bely, Levti Norisa; Bahri, Saiful; Mustari, Mukarramah (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: The purpose of this study is 1) To find out whether there is a significant effect with the Advanced Organizer learning model 2) To improve the cognitive abilities of students on the subject of dynamic fluid Vocational High School. The method used in this study is quasi-experimental with the hypothesis that there is no significant influence on the cognitive abilities of students who are taught using advance organizer learning models so that the cognitive abilities of students are increased. The results of this study indicate that there is a significant influence on the cognitive abilities of students who are taught using an advanced organizer model so that the cognitive abilities of students increase. This can be seen from the results of the pretest and posttest in the experimental class has increased. Significant influence can be proven by the test results from the t-test analysis, where in the t-test analysis the value of t-count more than t-table or significant value  less than significant level (0.05) is equal to 21,921 more than 2,045. While the increase in cognitive abilities of experimental class students can be seen from the results of the mean mean value of students at the pretest that is 40.16, an increase after the posttest results of the mean mean becomes 81.94. This means that there is a very good increase in the cognitive abilities of students due to the influence of the Advanced Organizer of Dynamic Fluid SMK models.Abstrak: Tujuan pada penelitian ini adalah 1) Untuk mengetahui apakah terdapat pengaruh yang signifikan dengan model pembelajaran Advance Organizer 2) Untuk meningkatkan kemampuan kognitif peserta didik pada pokok bahasan fluida dinamis  SMK. Metode yang digunakan pada penelitian ini adalah quasi eksperimen dengan hipotesis ada atau tidak pengaruh yang signifikan terhadap kemampuan kognitif peserta didik yang diajar dengan menggunakan model pembelajaran advance organizer sehingga kemampuan kognitif peserta didik lebih meningkat. Hasil dari penelitian ini menunjukkan bahwa terdapat pengaruh yang signifikan terhadap kemampuan kognitif peserta didik yang diajar dengan menggunakan model advance  organizer sehingga kemampuan kognitif peserta didik meningkat. Hal ini dapat dilihat dari hasil pretest dan posttest pada kelas eksperimen mengalami peningkatan. Pengaruh signifikan dapat terbukti dengan adanya hasil pengujian dari analisis Uji-t ,dimana pada analisis Uji-t  nilai lebih dari atau nilai signifikan kurang dari taraf signifikan (0.05) yaitu sebesar 21.921 lebih dari  2.045. Sedangkan peningkatan kemampuan kognitif peserta didik kelas eksperimen dapat dilihat dari hasil rata-rata nilai mean peserta didik pada pretest yaitu 40.16, terjadi peningkatan setelah posttest hasil rata-rata nilai mean menjadi 81.94. Artinya terjadi peningkatan yang sangat baik pada kemampuan kognitif peserta didik akibat pengaruh dari model Advance Organizer pokok bahasan Fluida Dinamis SMK.